The Nurse Practitioner Role in United States of America within Transitional Care and Care Coordination Models - Mola, Ana (Cultura del cuidado, 2018)
coordination models which have been operationalized within targeted populations that havefiscally reduced healthcare costs in the USA. A context of future globalization application ofthese emerging models will be discussed.Background The USA healthcare is complicated and the need for care coordination acrosssystems and providers is essential to maintain quality of care. NPs are ideally positioned to actas leaders and clinicians both within and beyond the health care organization to deliver patientcentric transitional care and care coordination models in the heart failure, geriatrics, palliativecare and mental health populations.Evaluation From the available research evidence, several support structures and mechanismsare identified as enablers for NPs to enact their leadership role in transitional care and carecoordination models.